Characterization and Pharmacokinetic Evaluation of Oxaliplatin Long-Circulating Liposomes - Cheraga, Nihad (Biomed Res Int, 2021)
The clinical efficacy of Oxaliplatin (L-OHP) is potentially limited by dose-dependent neurotoxicity and high partitioning to erythrocytes in vivo. Long-circulating liposomes could improve the pharmacokinetic profile of L-OHP and thus enhance its therapeutic efficacy and reduce its toxicity. The purpose of this study was to prepare L-OHP long-circulating liposomes (L-OHP PEG lip) by reverse-phase evaporation method (REV) and investigate their pharmacokinetic behavior based on total platinum in rat plasma using atomic absorption spectrometry (AAS). A simple and a sensitive AAS method was developed and validated to determine the total platinum originated from L-OHP liposomes in plasma. Furthermore, long-circulating liposomes were fully characterized in vitro and showed great stability when stored at 4°C for one month. The results showed that the total platinum in plasma of L-OHP long-circulating liposomes displayed a biexponential pharmacokinetic profile with five folds higher bioavailability and longer distribution half-life compared to L-OHP solution. Thus, long-circulating liposomes prolonged L-OHP circulation time and may present a potential candidate for its tumor delivery. Conclusively, the developed AAS method could serve as a reference to investigate the pharmacokinetic behavior of total platinum in biological matrices for other L-OHP delivery systems.